Análisis de técnicas de motivación efectiva y su incidencia en el desempeño laboral de la Empresa “Esquimasa” en la ciudad de Quevedo, año 2015 - Alcívar Montes, Lorena Lourdes (2015)
The present investigation was designed to analyze the impact on motivation and job performance of the employees of the company "ESQUIMASA". For data collection it was used a survey through a questionnaire of 10 questions, which was applied to a sample of 24 workers. The data were tabulated using Excel format, then the respective analysis indicated that the staff working in the company, presents a motivational level low, the lack of salary incentives, poor training, lack of motivational techniques and others that lead to determine that the working environment of the organization is not ideal; as the motivational levels are far from stimulating work performance, dissatisfaction, lack of motivation and job dissatisfaction negatively it affects the performance of their duties.